Pathogenesis of intestinal cryptosporidiosis in conventional and gnotobiotic piglets - Vítovec, J; Koudela, B (Veterinary parasitology, 1992)
The pathogenesis of intestinal cryptosporidiosis was studied in 52 conventionally reared and 20 gnotobiotically reared piglets by inoculation with different doses of Cryptosporidium parvum oocysts. The prepatent period of C. parvum in both groups of animals were variable, depending on the number of oocysts administered. The patent period of C. parvum in conventionally reared piglets was 8 or 9 days; in gnotobiotic piglets cryptosporidia were found in feces until Day post infection (DPI) 16, when the last piglet was necropsied. Cryptosporidiosis in conventionally reared piglets is a self-limited diarrheal disease associated with morphological changes within the intestine. The most severe lesion was seen in the posterior jejunum and ileum from DPI 3 to DPI 7, and consisted of villous atrophy, crypt hyperplasia and inflammatory infiltration in the lamina propria. In gnotobiotic piglets cryptosporidia induced severe enterocolitis which occurred at least until DPI 16. The characteristics of enteric lesions were similar to those found in conventionally reared piglets. Intestinal cryptosporidiosis in both groups of animals shifted in the course of infection in the caudal direction and terminated in the large intestine. Examination by scanning electron microscope showed that infected absorptive cells had thicker and longer microvilli than those on non-infected cells; neighboring non-infected cells were hypertrophic, bulbously protuberant with minute microvilli with no distinct intercellular borders. Numerous cryptosporidia in the heterotopic glandular epithelium in the submucosa of cecum and colon on DPI 9 and 10 were found. No differences in the location and degree of cryptosporidial infection between colostrum-fed and colostrum-deprived conventionally reared piglets were found. Sow's colostrum does not appear to protect piglets from C. parvum infection. The role of intestinal microflora in the pathogenesis of cryptosporidiosis in piglets is discussed.
Keywords: prasata; Animals; Cryptosporidium parvum; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; tlusté střevo; Swine Diseases; feces; nemoci prasat; Intestine, Small; Diarrhea; Feces; Intestine, Large; zvířata; tenké střevo; Germ-Free Life; kolostrum; kryptosporidióza; Colostrum; gnotobiologické modely; průjem; Swine; Cryptosporidiosis